Anterior temporal encephaloceles: Elusive, important, and rewarding to treat. (23rd October 2020) - Tse, Gabrielle T.; Frydman, Aviva S.; O'Shea, Marie F.; Fitt, Greg J.; Weintrob, David L.; Murphy, Michael A.; Fabinyi, Gavin C.; Bulluss, Kristian J.; Cook, Mark J.; Berkovic, Samuel F.
Abstract: Objective: To investigate the etiology and longitudinal clinical, neuropsychological, psychosocial, and surgical outcome profile of patients with medication refractory epilepsy and temporal encephaloceles with a view to highlight diagnostic clues and management strategies. Methods: The comprehensive epilepsy program databases at two surgical epilepsy centers from January 2000 to October 2018 were reviewed for this observational study, to identify patients with encephaloceles causing temporal lobe epilepsy (TLE) and treated with surgical resection. Their clinical, radiological, neuropsychological, psychiatric, and surgical data were obtained. Body mass index (BMI) data were also reviewed due to possible correlation between idiopathic intracranial hypertension and encephaloceles. Results: Thirteen patients (eight female) were identified; only three were recognized on initial magnetic resonance imaging (MRI) report. Temporal encephaloceles were identified on the left in eight patients, on the right in three patients, and bilaterally in two patients. One patient had a strong family history of encephaloceles. The median BMI for patients with seizure onset ≤20 years of age was 22.4, whereas for patients with onset >20 years median BMI was 32.6 ( P = .06). Five patients underwent a focal lesionectomy, three patients had limited temporal lobectomy, and five patients had standard anterior temporal lobectomy. Median postoperative follow‐up was 5.5 years. All but one patient were free of disabling seizures. Nine of ten neuropsychologically tested patients had no discernable cognitive decline postoperatively. Postoperative psychosocial adjustment features were present in four patients. Significance: Genetic factors and a possible association with idiopathic intracranial hypertension (given female predominance and elevated BMI) may contribute to the causation of temporal lobe encephaloceles. It is notable that a targeted surgical approach in the management of patients with TLE associated with encephaloceles has an excellent long‐term clinical and neuropsychological outcome. Subtle encephaloceles should be actively searched for in patients with drug‐resistant TLE because they significantly change surgical strategy and prognostication.